Continuous monitoring of colonoscopy performance in the Netherlands: first results of a nationwide registry - Nass, Karlijn J.; van der Schaar, Peter J.; van der Vlugt, Manon; Ledeboer, Michiel; van Esch, Aura A. J.; van der Beek, Sander; Lacle, Miangela M.; van Leerdam, Monique E.; Ouwendijk, Rob J. T.; Spaander, Manon C. W.; Wouters, Michel W. J. M.; Fockens, Paul; Dekker, Evelien (Endoscopy, 2021)
Background To optimize colonoscopy quality, several performance measures have been developed. These are usually assessed without distinction between the indications for colonoscopy. This study aimed to assess the feasibility of linking two national registries (one for colonoscopy and one for adverse events of gastrointestinal endoscopies in the Netherlands), and to describe the results of colonoscopy quality per indication.Methods This retrospective study was conducted with prospectively collected data of the Dutch Gastrointestinal Endoscopy Audit (DGEA) and the Dutch Registration of Complications in Endoscopy (DRCE). Data between 01–01–2016 and 01–01–2019 were analyzed. To calculate adverse event rates, data were linked at the level of endoscopy service.Results During the 3-year study period, 266 981 colonoscopies were recorded in DGEA. Of all indications, cecal intubation rate was highest in fecal immunochemical test (FIT)-positive screening colonoscopies (97.1 %), followed by surveillance (93.2 %), diagnostic (90.7 %), and therapeutic colonoscopies (83.1 %). The highest rate of adequate bowel preparation was observed in FIT-positive screening colonoscopies (97.1 %). A total of 1540 colonoscopy-related adverse events occurred (0.58 % of all colonoscopies). Bleeding and perforation and rates were highest for therapeutic (1.56 % and 0.51 %, respectively) and FIT-positive screening (0.72 % and 0.06 %, respectively) colonoscopies. The colonoscopy-related mortality was 0.006 %.Conclusion This study describes the first results of the Dutch national colonoscopy registry, which was successfully linked to data from the national registry for adverse events of gastrointestinal endoscopies. In this large dataset, performance varied between indications. Our results emphasize the importance of defining benchmarks per indication in future guidelines.